Affirming and Extending Professional Visions of Equitable Teaching: Managing Dilemmas in Teacher-Researcher Collaboration - Bryant Jensen; Aliza Segal; Taylor Topham; Adam Lefstein (AERA Open)
Learning to teach equitably is as knotty as equitable teaching itself. Both encompass challenges that place valid interests, such as efficiency and deliberation, into productive tension with one another. Applying Magdalene Lampert’s notion of “dilemma management” to teacher-researcher collaborations, we conduct a post-hoc analysis of negotiations in professional visions of equitable teaching between a researcher and a fifth-grade team of teachers in Hawai‘i. Using a formative peer observation system called Instructional Conversations for Equitable Participation (ICEP), this team used, questioned, and deviated from ICEP materials in their collaboration meetings to plan for and study equitable dialogic teaching practices in their mathematics lessons. Teachers appropriated, pushed back against, and adapted codes from ICEP observation rubrics to negotiate visions of equitable teaching that resonated with their students and the local context. We share implications for teacher-researcher collaboration and scaling and sustaining designs to assist rather than impose professional visions of equitable teaching.